Gambaran Kualitas Air Sumur Berdasarkan Parameter Fisik dan Derajat Keasaman (pH) - Miftahul Jannah S; Moh. Gazali (Jurnal Sanitasi Profesional Indonesia, 2025)
Clean water is a fundamental need that must be fulfilled at all times. Approximately 70% of the human body consists of water (Kumala et al., 2029). However, the availability of clean water that is safe for human consumption is very limited. Clean water intended for consumption must meet health standards, including physical, chemical, and bacteriological requirements (Fadli, 2022; Ministry of Health, 2023; Hiola et al., 2022). The most commonly used clean water facilities in both urban and rural areas are dug wells (FS et al., 2022). Contamination of clean water in dug wells is influenced not only by the presence and quantity of pollution sources such as seepage from latrines, animal pens, and domestic wastewater drainage systems (SPAL) surrounding the well but also by the physical construction of the well, including the height of the well curb, well walls, well flooring, SPAL condition, and the distance between the well and pollution sources (Sari, 2021; Asih, 2019; Agrelo, 2020; Rohmania et al., 2022).This study aims to describe the quality of dug well water based on physical parameters and acidity level (pH) in RT 12 and RT 14 at Grand Korpri Housing, Bentiring Subdistrict, Bengkulu City. The research used a descriptive method with a total of 13 dug well samples selected using purposive sampling. Examinations were conducted on physical parameters (TDS, turbidity, odor, temperature) and chemical parameters (pH) using a test kit, and the results were compared with the clean water quality standards based on Ministry of Health Regulation No. 2 of 2023, followed by an intervention using alum (tawas).The results showed that the TDS parameter met the quality standard. Meanwhile, 23.1% of turbidity parameters did not meet the standard, 38.5% of odor parameters did not meet the standard, 7.7% of temperature parameters did not meet the standard, and the pH parameter did not meet the standard. The intervention using 100 grams of alum per well resulted in a decrease in turbidity levels from 85.2 to 25.1 NTU, while TDS, pH, odor, and temperature showed no change.